peningkatan hasil belajar siswa pada pembelajaran Pkn menggunakan model Problem Based Learning di kelas V sekolah dasar - khairat, hasnatul; alwi, elma; nasrul, drs (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This research aims was to describe the improvement of the students’ on learning Civics using PBL model. Using qualitative and quantitative approach . Type of research that is research action class . This Subject of this research an teachers and students. Students as many as 20 people .The research procedure includes (1) planning, (2) implementation, (3) observation, and (4) reflection. The result of the research indicated that the student`s learning achievement improved first cycle  from average of 76.99 with qualification fication Good (B) and second cycle  average 84.91 with excellent qualification (SB) Hence, the use of Problem Based Leammg (PBL) model can improve student learning outcomes in elementary school (SD)